ANALISIS MUTU PELAYANAN TERHADAP BRAND IMAGE DAN LOYALITAS PELANGGAN - Aspizain Chaniago (POLITEKNIK LP3I JAKARTA, 2015)
This study was conducted to analyze the relationship between quality of service to brand image and customer loyalty. This research method is done through a survey method that is research done by taking a sample of the population and the use of a questionnaire as a data collection tool. Methods of data analysis using descriptive statistical analysis is needed to determine the frequency distribution of the questionnaire respondents, is by collecting data from the respondents' answers, then tabulated in tables and analyzed descriptively. Then performed inferential statistical analysis using analysis of structural equation model (The Structural Equation Modeling or SEM, from this analysis showed research that: Quality of service direct effect on brand image, means the better the value of service quality the better the value brand image. Quality of service effect on customer loyalty, means the better the quality of service value the better the value of customer loyalty and brand image not significant effect on customer loyalty, meaning that the results of the study can’t prove the existence of a significant effect of brand image on customer loyalty.Keywords: Service Quality, Brand Image, Customer Loyalty.